90Y-90SR DISEQUILIBRIUM IN SURFACE WATERS: INVESTIGATING SHORT-TERM PARTICLE DYNAMICS BY USING A NOVEL ISOTOPE PAIR - Orlandini K.A.; Bowling J.W.; Pinder J.E.; Penrose W.R. (My University, 2003)
We demonstrate the use of the disequilibrium between 90Sr (t1/2=29.1 yr) and its particle-reactive daughter 90Y (t1/2=64 h) to estimate particle removal rates and settling velocities in the epilimnion of a freshwater lake during varying conditions of stratification caused by seasonal changes. The estimated rates of removal obtained from the 90Sr–90Y disequilibrium showed good agreement with (a) measured rates of mass removal obtained from settling particle fluxes in sediment traps and the inventories of suspended material and (b) independently obtained removal coefficients for the scavenging behavior of two different isotopes of particle-reactive plutonium, present in the water column because of different processes. Because 90Sr is widespread and readily measurable in freshwater systems as a result of fallout from nuclear weapons testing, the 90Sr–90Y disequilibrium is a potentially valuable resource for examining particle dynamics in surface waters.